Preparation and application of multi-walled carbon nanotubes/poly(vinylidene fluoride-co_hexafluropropylene) composite membranes for filtration and adsorption of contaminants in water - Macevele, Lutendo Evelyn (My University, 2019)
This work presents the synthesis, characterisation and application of poly(vinylidene fluoride-co-hexafluropropylene) (PVDF-HFP) membrane prepared using a phaseinversion method. PVDF-HFP was blended with either functionalised multi-walled carbon nanotubes (MWCNTs), poly-amidoamine (PAMAM) dendrimeric MWCNTs or silver (Ag) nanoparticles and their combinations. Nanocomposite blends such as MWCNTs/PVDF-HFP, PAMAM-MWCNTs/PVDF-HFP, Ag-MWCNTs/PVDF-HFP and Ag-PAMAM-MWCNTs/PVDF-HFP were synthesised successfully. A variety of PVDF-HFP composite membranes prepared were characterised by X-ray powder diffraction (XRD), fourier transform infrared (FTIR), thermogravimetric analysis (TGA), Brunauer-Emmett-Teller (BET), scanning electron microscopy (SEM) and contact angle. The fMWCNTs, Ag-MWCNTs, PAMAM-MWCNTs and Ag-PAMAMMWCNTs nanocomposites were further characterised by Transmission electron microscopy (TEM) and energy dispersive X-ray (EDX). FTIR spectra of PAMAMMWCNTs confirmed the formation of functional groups such as COOH, NCO, NH2 and PAMAM dendrimer. XRD analysis demonstrated that the crystallite sizes of the silver nanoparticles were larger (8.4 nm) than those of Ag-MWCNTs (7.8 nm) and Ag-PAMAM/MWCNTs (6.4 nm) nanocomposites. These findings were further confirmed by TEM analysis which showed Ag nanoparticles, Ag-MWCNTs and Ag-PAMAM/MWCNTs having diameters of silver particles between 9 to 20 nm, 5 to 10 nm and 4 to 8 nm respectively. The reduced Ag particle sizes was due to the complexation of MWCNTs and PAMAMMWCNTs with Ag metal ions, which correlates with an enhanced surface area in the nanocomposite membranes, leading to good filtration and antibacterial properties. TGA studies demonstrated that the thermal stability of PVDF-HFP composite membrane was greatly enhanced by the addition of PAMAM-MWCNTs. However, the composite membranes consisting of both Ag nanoparticles and MWCNTs on PVDFHFP did not improve the structural stability of PVDF-HFP. All composite membranes have shown stability up to 400 oC. The contact angle, porosity, swellability and water content measurements of the composite membranes were improved showing enhanced hydrophilicity due to addition of MWCNTs, PAMAM-MWCNTs and/or Ag nanoparticles. The scanning electron microscopy (SEM) images have depicted the formation of microporous structure, with few MWCNTs on the surface strongly interacting with PVDF-HFP as demonstrated by TGA, XRD and FTIR data. SEM cross-sections of PVDF-HFP composite membranes showed a mixture of fingure-like microvoids with a membrane diameter of approximately 180 μm. The BET data showed an improved surface area, pore volume and pore sizes of PVDF-HFP composite membranes when blended with fMWCNTs and PAMAM. These membranes also showed high fouling resistance, good desalination and high Cd(II) ions rejections during permeability studies. E. coli filtration studies indicated that 2.5 wt.% Ag-MWCNTs/PVDF-HFP and 1.8 wt.% Ag-PAMAM-MWCNTs/PVDF-HFP composite membranes displayed good microbial load reduction (100%) and excellent antibacterial properties as evidenced by the bacterial growth on the edges of the membranes. The microbial, physicochemical and chemical analysis of surface water samples from Sekhukhune area showed that the water was contaminated with Enterobacteriaeceae, E. coli, total coliform with high turbidity and total suspended solids above the South African national standard (SANS 241) water guidelines. After filtration with 1.8 wt.% Ag-MWCNTs/PVDF-HFP composite membrane, turbidity was reduced to 4 Nephelometric turbidity units (NTU), total suspended solids to 1 mg/L while Enterobacteriaeceae, E. coli and total coliform were undetectable and complied with SANS 241 limits. Chromium concentration levels were reduced from 0.194 to 0.0138 mg/L, after filtration with 1.8 wt.% Ag-PAMAM-MWCNTs/PVDF-HFP composite membrane also within acceptable SANS 241 limits. Adsorption studies of all composite membranes demonstrated that the adsorption processes of Cd(II) ions was well conformed to Freundlich model (R2 = 0.999), which suggests that the sorption process met heterogeneous adsorption. However, for Cr(VI) ions studies, the adsorption process was conformed to both Langmuir (R2 = 0.999) and Freundlich (R2 = 0.998) model which suggest that that the adsorption process meet both monolayer and heterogeneous adsorption. The maximum adsorption capacity fitted by Langmuir isotherm was 166.7 and 9.72 mg/g for Cd(II) ions (at optimum pH 6.5) and Cr(VI) ions (at optimum pH 2.5) respectively, using 1 wt.% PAMAM-MWCNTs/PVDF-HFP composite membrane. The adsorption capacities of Cd(II) ions were higher than those of Cr(VI) ions, which is thought to be due to the properties of the composite membrane material. According to the thermodynamic parameters, the Cd(II) and Cr(VI) ions adsorption process was spontaneous and endothermic. Reusability studies showed that PVDF-HFP composite membranes can be reused at least 4 times with an adsorption loss of only 5% for 1 wt.% PAMAMMWCNTs/PVDF-HFP composite membrane, confirmed by TGA and ICP-OES analysis. The 1 wt.% PAMAM-MWCNTs-PVDF-HFP composite membrane exhibited a higher selectivity towards Cd(II) over Cu(II), Zn(II) and Ni(II) in binary and quaternary metal adsorption studies.
Thesis (Ph. D. (Chemistry)) -- University of Limpopo, 2019
Keywords: Characterisation of poy(vinylidene fluoride-cohexafluropropylene); Adhesion; Chemistry